A simple analytical model for bamboo-reinforced slopes using modified Bishop method - Chakrabortty, Pradipta; Srivastava, Lokesh Sharan; Kumar, Pintu (Frontiers in Built Environment, 2023)
Embankments are constructed at many places to serve the purpose of transportation like railways, roadways, etc. The stability of slope in embankment has always been a matter of concern, especially in cohesionless soil. There are many methods to increase the factor of safety of cohesionless soil slopes using geogrid, geocell, concrete pile, etc. The conventional material used for the stabilization of slopes has a huge impact on the environment. Nowadays researchers are using natural fibers such as bamboo, coir fiber, etc. for stabilization purposes. In this paper, bamboo piles are used for the stabilization of the slope. The bamboo piles are inserted vertically at the slope face to increase the shear strength and stability against slope failure. A limit equilibrium method has been developed for estimating the stability of slope improved by friction piles after modification of Bishop’s method of slices. The stability of slope is analyzed for both conditions namely, reinforced condition and unreinforced condition using the developed analytical formula. Analytical equations were developed by considering three cases of slope failure i.e., shearing failure of bamboo piles along the failure surface, moving of upper part of soil leaving bamboo pile behind embedded in the base soil and pulling out of bamboo along with upper part of the soil mass. Further validation of the results is done with the limit equilibrium method-based software SLOPE/W by using modified Bishop’s method. It has been observed that the factor of safety increased after reinforcing the slope with bamboo piles for all three cases.